Speak Louder Than the Ballot: A Cognitive Study to Election Abstention Metaphors - Muhammad Adam (k@ta: A Biannual Publication on the Study of Languange and Literature, 2021)
There have been few studies that highlight the use of metaphor in political discourse and election, but none of those studies focus on the election abstention –known in Indonesia as Golput phenomena- and the discussion of the intertwined components in metaphor. This research aims to investigate various metaphor components in the metaphorical description used to describe the abstention during the Indonesian election 2019 within the Conceptual Metaphor Theory (Lakoff and Johnson, 1980). Kovecses (2003) highlighted components of metaphor are also used to examine the essential components of conceptual metaphor in the use. The sources of data were from five foreign media reports that discuss the Indonesian issue of election abstention. The result shows there few essential components that can be revealed behind a metaphor such as the importance of mental image, cultural context, and highlighted elements in metaphor that contribute to the metaphorical function and interpretation